#Oculoplastics: An Analysis of TikTok's Top Oculoplastics Content. Issue 5 (23rd March 2022) - Cheng, Tiffany; Wang, Fei; Barmettler, Anne
Abstract : Purpose: To analyze the source and quality of oculoplastics-related content on TikTok, a popular social media platform. Methods: Twenty-five oculoplastics-related hashtags were queried. The top 20 videos for each hashtag were included. The number of views, likes, comments, and shares were recorded for each video. Each video was also categorized by the account owner and by video content characteristics. A subanalysis of the educational videos was conducted using the mDISCERN, Patient Education Materials Assessment Tool, and modified MICI scores to assess video quality, understandability and actionability, and medical accuracy, respectively. Results: The included 386 videos amassed 218, 997, 134 views, 15, 033, 220 likes, 148, 099 comments, and 276, 445 shares. Patients were the leading content creators (38.1%), followed by nonophthalmology MDs/DOs (25.6%), and oculoplastic surgeons/ophthalmologists (16.3%). Physician-created videos received more visibility than nonphysician-created videos (median of 23, 600 views and 22 shares), though this did not reach statistical significance. However, oculoplastic surgeon-posted content received the lowest median views and shares. The video category that amassed the most views was "live procedure/surgeries, " followed by "educational" and "patient experience." Subanalysis of 46 educational videos revealed physicians were the chief creators, accounting for 67.4% of all educational videos. Physician-created content demonstrated statistically significant better understandability and actionability, as measured by the Patient Education Materials Assessment Tool ( p = 0.0053). Conclusion: Physicians play an important role in disseminating evidence-based medicine on social media. While oculoplastics-related TikTok videos are gaining traction, additional research is needed to improve the visibility of oculoplastic-surgeon posted content. Abstract : While oculoplastics-related content is gaining popularity on TikTok, videos posted by oculoplastic surgeons were viewed the least compared with other content creators, indicating that research is needed to improve visibility of oculoplastic surgeons on the application.